The Bai'at Santri System of Islamic Unity Islamic Boarding Schools in Indonesia as An Effort to Deradicalize Religious Behavior - Saebani, Beni Ahmad; Mustopa, Mustopa (Westscience Press, 2023)
One of the Islamic boarding schools that is known to be quite fundamental in implementing an understanding of Islamic teachings is the Islamic Association Islamic Boarding School. The main sources of Islamic teachings which are the benchmark for truth in all actions, especially those related to faith and sharia are the Koran and al-Hadith. However, if there is minimal development of interpretive methodology for these two sources, it will result in exclusive religious behavior and truth claims for one's own opinions. So, it is not uncommon for this understanding to give rise to cultural conflicts in society where some parties have long practiced traditional Islamic religion and give rise to radical thought patterns and actions. The fundamental and radical thinking pattern which is interpreted politically is not without reason, but refers to various terrorist incidents which when the perpetrators were interviewed and books which were used as references for acts of terrorism indicated radical, takfiri and truth claim thinking patterns which were then aimed at educational products. Deradicalism means eliminating radical actions or radicalism, eliminating all ideologies and currents that give rise to acts of violence and terror. This gives rise to religious radicalism which, at a certain level, gives rise to acts of terror as an implementation of the concept of jihad which causes victims in an inhumane way. The research method uses descriptive analysis with qualitative data types and a sociological approach. The type of data is adjusted to the research objectives, while the primary data source is the caregivers and students of Islamic Association Islamic boarding schools in West Java, East Java and Central Java. Secondary data is in the form of students' allegiance documents, books about the Islamic Association, and profiles of the Islamic Association Islamic boarding school, the tertiary data is all scientific works that support this research. Data was collected by observation, interviews, documentation and literature study. The data collected was analyzed using the content analysis method.